German experiences in documenting and presenting information about past crimes to the public - Nikolić-Ristanović Vesna (Temida, 2012)
This paper aims to present German experiences in documenting the crimes of the past using Berlin as a case study. The first part provides a brief overview of the history and the broader social context in which the process of dealing with the past took place in Germany in general, and in Berlin in particular, as well as the most important characteristics of data on crimes that were presented to the public. The second part provides an overview and analysis of the data presented in two memorials: the Topography of Terror and the Memorial to the Murdered Jews of Europe. These two memorials are examples of presenting information about war crimes that can be considered as fairly inclusive, thus the goal of their presentation is to highlight the potential that these approaches may have in creating a social memory and the overall attitude of society toward the past. The findings presented in this paper are the result of the research carried out by the author in Berlin in June 2011. [Projekat Ministarstva nauke Republike Srbije, br. 179044 Razvoj metodologije evidentiranja kriminaliteta kao osnova kreiranja efikasnih mera za njegovo suzbijanje i prevenciju]